Polymer capable of simultaneously releasing far infrared rays and negative ions and preparation method thereof

By reasonably preparing small molecule pure water slurry, epoxy resin emulsion and other components in polymers, and using specific preparation methods, the coordinated release of far infrared rays and negative ions is achieved, solving the insufficient release amount and weather resistance of existing products. The problem of this paper achieves efficient negative ions and far infrared release, improving the wear resistance of the paint and promoting human health.

CN119410224AActive Publication Date: 2025-02-11BEIJING SHENGSHENG ENVIRONMENTAL TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411267422.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-11
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing market lacks products that can release high negative oxygen ions and far infrared rays at the same time. The release amount and weather resistance of some products are insufficient and the attenuation speed is fast.

Method used

A polymer is used, and its raw material components include small molecule pure aqua slurry, epoxy resin emulsion, propylene glycol, epoxy curing agent, imidazole dispersion additive, rutile titanium dioxide powder, light rare earth powder, coating interface agent and Special ore powder can achieve the coordinated release of far infrared rays and negative ions through specific ratios and preparation methods.

Benefits of technology

A high negative oxygen ion release (3000~6000 pieces/cm3, higher than the national standard), and the infrared and negative ions release of the polymer increases with the increase of temperature, with a slow attenuation rate, and the annual attenuation is not greater than that of The average occurrence of 1.2% in the previous year also improved the wear resistance of the paint and the human health promotion effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410224A_ABST
    Figure CN119410224A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer capable of simultaneously releasing far infrared rays and negative ions and a preparation method thereof. Comprising the following components in parts by weight: 0.1-45% of micromolecular pure water color paste, 40-85% of epoxy resin emulsion, 0.1-3% of propylene glycol, 2-10% of an epoxy curing agent, 0.5-5% of an imidazole dispersing aid, 0.2-12% of rutile titanium dioxide powder, 2-10% of light rare earth powder, 2-21% of a coating interface agent and 0.5-10% of special mineral powder. The prepared polymer can release far infrared rays and negative ions at the same time, the attenuation of each year is not larger than 1.2% of the average generation amount of the last year, the amount of released negative ions is 3000-6000 / cm < 3 >, and when the polymer is applied to different places and fields, metabolism of a human body can be promoted, and human health is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a polymer capable of simultaneously releasing far infrared rays and negative ions and a preparation method thereof. Background Art

[0002] Negative ions, also known as negative oxygen ions, refer to oxygen ions that have gained one or more electrons and carry a negative charge. Negative oxygen ions are beneficial to the physical and mental health of the human body, can enhance blood energy, promote blood circulation, and enhance the body's immune function. Being in an environment with high levels of negative oxygen ions will make people feel refreshed. It mainly has the effects and functions of protecting the environment, maintaining physical health, and curing certain diseases.

[0003] The national standard for negative oxygen ions means that the concentration of negative oxygen ions in fresh air should be greater than 1000-1500 per cubic centimeter; the World Health Organization stipulates that the standard concentration of negative oxygen ions in fresh air should be greater than 1000-1500 per cubic centimeter. Research shows that air quality can be divided into six levels according to the concentration of negative oxygen ions. Below 600 per cubic centimeter is very detrimental to human health; the fourth level concentration of 1200-1800 per cubic centimeter can kill and reduce disease infection; the fifth level concentration of 1800-2100 per cubic centimeter gives people natural healing power; and reaching the sixth level of 2100 per cubic centimeter or more has therapeutic and rehabilitation effects, which is extremely beneficial to human health.

[0004] Far infrared rays have strong penetration and radiation power, significant temperature control effect and resonance effect, and are easily absorbed by objects and converted into internal energy of objects. After being absorbed by the human body, far infrared rays can cause water molecules in the body to resonate, activate water molecules, and enhance the binding force between molecules, thereby activating biological macromolecules such as proteins, and making biological cells at the highest vibration energy level. Due to the resonance effect of biological cells, far infrared heat energy can be transferred to the deeper part of the human body's subcutaneous tissue, and the temperature of the deep layer below rises, and the generated warmth is radiated from the inside to the outside. This intensity of action causes capillaries to expand, promotes blood circulation, strengthens metabolism between tissues, increases tissue regeneration capacity, improves the body's immune capacity, and regulates abnormal excitement of the mind, thereby playing a role in medical care.

[0005] At present, the products with good environmental indicators and wide application in the international market, such as water-based paints and children's paints, meet the standards in terms of radioactivity and formaldehyde content, but there are no products on the market that can release both negative ions and far infrared rays at the same time. Some products that claim to be able to release them have small release amounts and weather resistance, and decay quickly.

[0006] Therefore, how to use negative oxygen ions to maintain human health and promote physical recovery, develop materials that can simultaneously release high levels of negative oxygen ions and far infrared rays, and apply them in different fields to achieve the effect of promoting human health is what the current technology in this field lacks. Summary of the invention

[0007] Based on the above deficiencies in the prior art, the present invention provides a polymer that can simultaneously release far infrared rays and negative ions and a preparation method thereof, which solves the problem of how to use far infrared rays and negative oxygen ions to maintain human health and promote physical recovery, and develops materials that can simultaneously release far infrared rays and negative oxygen ions, which can be applied in different fields to promote human health.

[0008] The technical solution adopted by the present invention to solve the above technical problems is as follows: A polymer capable of releasing far infrared rays and negative ions simultaneously, wherein the raw material components and the weight ratio of the components are as follows: 0.1-45% of small molecule pure water color paste, 35-75% of epoxy resin emulsion, 0.5-3% of propylene glycol, 2-10% of epoxy curing agent, 0.5-5% of imidazole dispersing aid, 1-12% of rutile titanium dioxide powder, 2-10% of light rare earth powder, 2-21% of coating interface agent and 0.5-10% of special mineral powder.

[0009] The special mineral powder is at least three of tourmaline, rare crystal stone, longevity stone, cassia stone and six-ring stone.

[0010] The raw material components and the weight ratio of each component are: small molecule pure water color paste 15-45%, epoxy resin emulsion 50-75%, propylene glycol 1.5-3%, epoxy curing agent 3-5%, imidazole dispersing aid 0.5-5%, rutile titanium dioxide powder 5-8%, light rare earth powder 2-6%, coating interface agent 2-5% and special mineral powder 4-7%.

[0011] The special mineral powder is four or five of tourmaline, rare crystal stone, longevity stone, osmanthus stone and six-ring stone.

[0012] The raw material components and the weight ratio of each component are: 20% small molecule pure water color paste, 50% epoxy resin emulsion, 3% propylene glycol, 3% epoxy curing agent, 0.5% imidazole dispersing aid, 8.5% rutile titanium dioxide powder, 6% light rare earth powder, 2% coating interface agent and 7% special mineral powder; the raw materials of the special mineral powder are tourmaline: rare crystal stone: hexacyclic stone = 1:1:1.

[0013] The epoxy resin emulsion is selected from an epoxy equivalent of 100 to 200 g / mol; the epoxy curing agent is an alicyclic amine epoxy curing agent or an aromatic amine epoxy curing agent; the cation in the imidazole dispersing aid is one or two or three of 1,3-dimethylimidazolium cation, 1,2-dimethylimidazolium cation or 2,3-dimethylimidazolium cation.

[0014] The weight proportion of cerium group elements in the light rare earth powder is 0.5-5%; the coating interface agent is silver iodide and zinc dioxide, and the ratio of silver iodide to zinc dioxide is 30-70%:30-70%.

[0015] The particle sizes of the small molecule pure water color paste, epoxy resin emulsion, propylene glycol, epoxy curing agent, silver iodide powder, imidazole dispersing aid, rutile titanium dioxide powder, light rare earth powder, coating interface agent and special mineral powder are all nanometer grade.

[0016] A method for preparing a polymer capable of simultaneously releasing far infrared rays and negative ions comprises the following steps: S1. Prepare raw materials in proportion; S2, adding small molecule pure water color paste, epoxy resin emulsion, propylene glycol and imidazole dispersing aid into a reaction vessel for mixing and pre-dispersing to obtain a mixture, and the mixing and pre-dispersing time is 30 to 180 minutes; S3, dividing the mixture obtained in S2 into two parts, and putting them into the first reaction kettle and the second reaction kettle respectively; S4, putting silver iodide and rutile titanium dioxide powder into a first reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 1, and the polymerization reaction time is 60 to 180 minutes; S5, putting light rare earth powder, coating interface agent, epoxy curing agent and mineral mixed powder into a second reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 2, and the polymerization reaction time is 60 to 200 minutes; S6. Performing electrophoresis reaction on the obtained polymer 1 and polymer 2 at a voltage of 600 to 1000 V to generate a target polymer.

[0017] Compared with the prior art, the present invention is beneficial in that: The rutile titanium dioxide powder in the present invention can improve the appearance of the polymer and enhance the weather resistance and chemical stability of the polymer; the rare earth element of the light rare earth powder has a special electronic structure and optical properties, which helps to enhance the far-infrared release ability of the polymer; the silver iodide powder of the coating interface agent has the function of exciting ions in the structure of the polymer and has strong bactericidal properties; the zinc ions are used to stabilize the color state and improve the bonding performance between the polymer and the substrate; the special mineral powder can release far-infrared and negative ions.

[0018] The present invention uses rutile titanium dioxide powder, light rare earth powder, coating interface agent and special mineral powder at the same time, which work synergistically to produce the following effects: 1. High negative oxygen ion release: the amount of negative ions produced is 3000-6000 / cm 3 , which is higher than the national standard.

[0019] 2. Slow decay: When the polymer prepared by the preparation method of the present invention is used in coatings, water-based paints and expanded ceramic products, when the ambient temperature is 17°C-45°C and the ambient humidity is greater than 50%, the infrared and negative ion generation of the above products increases with the temperature rise, and the infrared and negative ion generation decays with the years of use, but the annual decay is no more than 1.2% of the average generation in the previous year.

[0020] 3. Good wear resistance: The polymer prepared by the preparation method of the present invention is used in the coating, which can make the coating have a wear resistance of more than 10,000 times and the coating area is greater than 12m 2 / kg does not affect its function.

[0021] 4. Beneficial to human health: The polymer prepared by the preparation method of the present invention can be applied to places such as sanatoriums, hospitals, infant protection rooms, etc., and has the effects of reducing formaldehyde content, sterilizing and removing dust, reducing the harm of secondhand smoke, anti-oxidation, and anti-aging. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Attached Figure 1 This is a curve diagram of the weather resistance test results of Example 4 of the present invention; Attached Figure 2 This is the first performance test result of Example 2 of the present invention; Attached Figure 3 The second performance test result 2 of Example 2 of the present invention; Attached Figure 4 This is the first performance test result 1 of Example 3 of the present invention; Attached Figure 5 This is the second performance test result 2 of Example 3 of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The invention discloses a polymer capable of releasing far infrared rays and negative ions at the same time. The raw material components and the weight ratio of each component are as follows: 0.1-45% of small molecule pure water color paste, 35-75% of epoxy resin emulsion, 0.5-3% of propylene glycol, 2-10% of epoxy curing agent, 0.5-5% of imidazole dispersing aid, 1-12% of rutile titanium dioxide powder, 2-10% of light rare earth powder, 2-21% of coating interface agent and 0.5-10% of special mineral powder, wherein the special mineral powder is at least three of tourmaline, rare crystal stone, Tianshou stone, Guibao stone and Liuhuan stone, wherein: (1) Raw materials Small molecule pure water color paste mainly provides color and hiding power, and also has good light resistance, weather resistance, acid resistance, alkali resistance and other properties. It has strong tinting power, small amount used during color adjustment, and little impact on coating performance, which helps to reduce color adjustment costs. At the same time, small molecule water can also prevent flash explosions and other problems caused by excessively fine powders during the production process.

[0025] The epoxy equivalent of epoxy resin emulsion is 100-200g / mol. Epoxy resin emulsion is the main component of polymer. Epoxy resin emulsion has excellent properties such as high mechanical strength, strong adhesion, low shrinkage and good stability. It forms a network of three-dimensional polymers through mixing and curing with other components, thus forming the basic structure of the composite material.

[0026] The addition of propylene glycol is used to improve the flexibility and processing properties of the polymer, and also helps to adjust the viscosity of the polymer to make it easier to apply.

[0027] The epoxy curing agent is an alicyclic amine epoxy curing agent or an aromatic amine epoxy curing agent. The epoxy curing agent is a key component that reacts chemically with the epoxy resin. It promotes the curing reaction of the epoxy resin, forms a strong network structure, and improves the hardness and durability of the polymer.

[0028] The cation in the imidazole dispersing aid is one, two or three of 1,3-dimethylimidazolium cation, 1,2-dimethylimidazolium cation or 2,3-dimethylimidazolium cation. The imidazole dispersing aid is mainly used to help each component to be evenly dispersed in the polymer to prevent precipitation or agglomeration, thereby ensuring the uniformity and stability of the polymer.

[0029] Rutile titanium dioxide powder is a raw material for making white pigments with excellent hiding power and tinting power. It can not only improve the appearance of polymers, but also enhance the weather resistance and chemical stability of polymers.

[0030] The main component of light rare earth powder is cerium group, and the weight range of cerium group elements is 0.5-5%. The addition of light rare earth powder is used to adjust the physical properties of polymers, such as thermal stability, mechanical strength, etc. At the same time, rare earth elements have special electronic structures and optical properties, which help to enhance the far-infrared release ability of polymers.

[0031] The coating interface agent is silver iodide and zinc dioxide, and the ratio of silver iodide to zinc dioxide is 30-70%:30-70%. Silver iodide powder and zinc dioxide powder play a role in catalyzing or assisting the release of far infrared rays and negative ions. Although silver iodide itself cannot directly release negative oxygen ions and far infrared rays, it has the function of exciting ions in the structure of the polymer, which helps to enhance the release effect of far infrared rays and negative ions. Silver ions have strong bactericidal properties, but they are easy to have a serious impact on chromaticity, so zinc ions are used to supplement and stabilize the color state. At present, silver and zinc compounds have been widely used in the medical field for small-scale disinfection and antibacterial. The coating interface agent is mainly used to improve the bonding performance between the polymer and the substrate, and to improve the adhesion and durability of the coating.

[0032] Special mineral powders are selected from three, four or five of tourmaline, rare crystal stone, longevity stone, osmanthus stone and six-ring stone. The raw materials are mixed in a ratio of 0.95:1 to 1:1.05. Adding special mineral powders can release far-infrared and negative ions. Tourmaline has special thermoelectricity and piezoelectricity, and can release a large number of negative ions when heated and pressed. In addition to negative ions, tourmaline can also radiate far-infrared rays, which are beneficial to the human body. Tourmaline can also absorb heavy metal ions and adjust the pH value of water; rare crystal stone can release far-infrared microwaves with the same frequency as the human body, and the far-infrared rays released can "resonate" with the water molecules of cells, effectively promoting cell growth; longevity stone, also known as Tianshou stone , can release negative oxygen ions and far infrared rays. The released negative oxygen ions can activate the iron in the body and help improve the blockage of sebaceous glands. The released far infrared rays can achieve resonance vibration of the human body and help accelerate metabolism. The combination of negative ions and far infrared rays can make blood and sweat finer and fresher; cinnamon gem can release negative ions and is rich in trace elements, which can dissolve minerals and regulate water quality; Liuhuan stone can form negative ions through the redox reaction of variable valence metals silver and zinc, combining with water molecules in the environment, and permanently releasing negative oxygen ions. It can emit far infrared rays with a vibration frequency close to that of human cells, which is beneficial to health. It can also generate bioelectricity, activate immune cells, and enhance phagocytic ability.

[0033] The particle size of small molecule pure water color paste, epoxy resin emulsion, propylene glycol, epoxy curing agent, silver iodide powder, dispersing aid, rutile titanium dioxide powder, light rare earth powder, coating interface agent and special mineral powder are all nanometer grade (2) preparation method The following steps are involved: S1. Prepare raw materials in proportion; S2, adding small molecule pure water color paste, epoxy resin emulsion, propylene glycol and imidazole dispersing aid into a reaction vessel for mixing and pre-dispersing to obtain a mixture, and the mixing and pre-dispersing time is 30 to 180 minutes; S3, dividing the mixture obtained in S2 into two parts, and putting them into the first reaction kettle and the second reaction kettle respectively; S4, putting silver iodide and rutile titanium dioxide powder into a first reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 1, and the polymerization reaction time is 60 to 180 minutes; S5, putting the light rare earth powder and the coating interface agent into the second reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 2, and the polymerization reaction time is 60 to 200 minutes; S6. Performing electrophoresis reaction on the obtained polymer 1 and polymer 2 at a voltage of 600 to 1000 V to generate a target polymer.

[0034] In the following examples and comparative examples, the small molecule pure water color paste used is a self-made material. The small molecule pure water of the present invention refers to the number of water molecules existing simultaneously on a single molecular chain being less than 10; the epoxy resin emulsion used is a formaldehyde-free resin of BASF (China) Co., Ltd.; the propylene glycol used is a USP grade of Dow Chemical Company or Shida Shenghua Company; the epoxy curing agent used is E-44 or E-51 of Shenzhen Borui Technology Co., Ltd.; the imidazole dispersing aid used is a standard nano-grade imidazole dispersing aid of Guangdong Lisheng Polymer Technology Co., Ltd.; the rutile titanium dioxide used is DuPont R902 of Jinan Hongquan Titanium Company; The light rare earth powder used is selected from the Northern Rare Earth Fluorocarbon Ce type, and the particle size grade is nanometer level; the coating interface agent used is Bayer or China Resources interface agent standard HPMC, in which the weight ratio of silver oxide and zinc dioxide is 1:1; the special mineral powder used is produced in Hebei, and the special mineral powder raw materials are mixed in equal weight ratios, and each raw material powder is processed to 30-50 nanometer level; it is specially noted that if the particle size of the imidazole dispersing agent, rutile titanium dioxide powder, light rare earth powder, coating interface agent and special mineral powder cannot reach the nanometer level, they must be deeply processed to reach the standard nanometer particle size, and at the same time, the particle size of silver iodide, light rare earth powder and special mineral powder must be guaranteed to be 30nm, and PDI=50.

[0035] The specific weight ratios of the components in each example are shown in Table 1.

[0036] Table 1: Raw materials and their weight ratio (unit: %) Embodiment 1: The polymer is prepared according to the weight ratio of Table 1, comprising the following steps: S1. Prepare raw materials according to the proportions in Table 1; S2, adding small molecule pure water color paste, epoxy resin emulsion, propylene glycol and dispersing aid into a reaction vessel for mixing and pre-dispersing to obtain a mixture, and the mixing and pre-dispersing time is 80 minutes; S3, dividing the mixture obtained in S2 into two parts, and putting them into the first reaction kettle and the second reaction kettle respectively; S4, putting silver iodide and rutile titanium dioxide powder into a first reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 1, and the polymerization reaction time is 90 minutes; S5, putting the light rare earth powder and the coating interface agent into the second reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 2, and the polymerization reaction time is 90 minutes; S6. Performing electrophoresis reaction on polymer 1 and polymer 2 obtained in S4 and S5 according to their activities to generate polymer 3, wherein the electrophoresis reaction adopts a voltage of 600V.

[0037] Embodiment 2: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 60 minutes, the reaction time of polymer one is 80 minutes, the reaction time of polymer two is 80 minutes, and the voltage of the electrophoretic reaction of polymer three is 700V.

[0038] Embodiment 3: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 120 minutes, the reaction time of polymer one is 100 minutes, the reaction time of polymer two is 100 minutes, and the voltage of the electrophoresis reaction of polymer three is 800V.

[0039] Embodiment 4: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 120 minutes, the reaction time of polymer one is 120 minutes, the reaction time of polymer two is 1200 minutes, and the voltage of the electrophoretic reaction of polymer three is 900V.

[0040] Embodiment 5: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 70 minutes, the reaction time of polymer one is 80 minutes, the reaction time of polymer two is 80 minutes, and the voltage of the electrophoretic reaction of polymer three is 850V.

[0041] Embodiment 6: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 50 minutes, the reaction time of polymer one is 70 minutes, the reaction time of polymer two is 70 minutes, and the voltage of the electrophoretic reaction of polymer three is 750V.

[0042] Embodiment 7: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 180 minutes, the reaction time of polymer one is 180 minutes, the reaction time of polymer two is 200 minutes, and the voltage of the electrophoretic reaction of polymer three is 950V.

[0043] Embodiment 8: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 40 minutes, the reaction time of polymer one is 60 minutes, the reaction time of polymer two is 60 minutes, and the voltage of the electrophoretic reaction of polymer three is 650V.

[0044] Embodiment 9: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 160 minutes, the reaction time of polymer one is 110 minutes, the reaction time of polymer two is 110 minutes, and the voltage of the electrophoresis reaction of polymer three is 1000V.

[0045] Embodiment 10: The adjustment of the formula ratio of this embodiment is detailed in Table 1. The specific implementation process is basically the same as that of Example 1, except that the mixing pre-dispersion time is 140 minutes, the reaction time of polymer one is 100 minutes, the reaction time of polymer two is 100 minutes, and the voltage of the electrophoresis reaction of polymer three is 1000V.

[0046] The polymers prepared in the above Examples 1-10 are formed into coating products, and the performance of the coating products is tested according to relevant industry standards under an environment of air humidity of 50% and room temperature of 25°C. Nippon paint for children's environmentally friendly coating is selected as comparative example 1. The relevant test results are shown in Table 2.

[0047] Table 2: Test results

[0048] Among them, Example 4 was selected to conduct a weather resistance experiment (i.e., a far infrared ray and negative ion generation amount change experiment) when the ambient temperature was 17°C-45°C and the ambient humidity was greater than 50%. The curve diagram of the experimental results is shown in the attached figure. Figure 1 As shown in the curve diagram, it can be seen that the weather resistance of Example 4 decays in a wave-like manner with the increase of time, and the annual decay amount is 0.5-1.2%. The occurrence amount is the lowest in winter every year, and increases with the increase of temperature and air humidity in spring, summer and autumn.

[0049] It can be seen from the test results that the amount of negative ions generated by the present invention is 3000-6000 / cm 3 , which is higher than the national standard; the polymer prepared by the present invention is used in coatings to make the coatings have a wear resistance of more than 10,000 times; the polymer prepared by the present invention can be applied to places such as sanatoriums, hospitals, infant protection rooms, etc., and has the effects of reducing formaldehyde content, sterilizing and removing dust, reducing the harm of secondhand smoke, anti-oxidation, and anti-aging.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polymer capable of simultaneously releasing far infrared rays and negative ions, characterized in that: The raw material components and the weight ratio of each component are: small molecule pure water color paste 0.1-45%, epoxy resin emulsion 35-75%, propylene glycol 0.5-3%, epoxy curing agent 2-10%, imidazole dispersing aid 0.5-5%, rutile titanium dioxide powder 1-12%, light rare earth powder 2-10%, coating interface agent 2-21% and special mineral powder 0.5-10%.

2. The polymer capable of simultaneously releasing far infrared rays and negative ions according to claim 1, characterized in that: The special mineral powder is at least three of tourmaline, rare crystal stone, longevity stone, cassia stone and six-ring stone.

3. The polymer capable of simultaneously releasing far infrared rays and negative ions according to claim 2, characterized in that: The raw material components and the weight ratio of each component are: small molecule pure water color paste 15-45%, epoxy resin emulsion 50-75%, propylene glycol 1.5-3%, epoxy curing agent 3-5%, imidazole dispersing aid 0.5-5%, rutile titanium dioxide powder 5-8%, light rare earth powder 2-6%, coating interface agent 2-5% and special mineral powder 4-7%.

4. The polymer capable of simultaneously releasing far infrared rays and negative ions according to claim 3, characterized in that: The special mineral powder is four or five of tourmaline, rare crystal stone, longevity stone, osmanthus stone and six-ring stone.

5. The polymer capable of simultaneously releasing far infrared rays and negative ions according to claim 2, characterized in that: The raw material components and the weight ratio of each component are: 20% small molecule pure water color paste, 50% epoxy resin emulsion, 3% propylene glycol, 3% epoxy curing agent, 0.5% imidazole dispersing agent, 8.5% rutile titanium dioxide powder, 6% light rare earth powder, 2% coating interface agent and 7% special mineral powder; the raw materials of the special mineral powder are tourmaline: rare crystal stone: hexacyclic stone = 1:1:

1.

6. A polymer capable of simultaneously releasing far infrared rays and negative ions according to any one of claims 1 to 5, characterized in that: The epoxy resin emulsion is selected from an epoxy equivalent of 100 to 200 g / mol; the epoxy curing agent is an alicyclic amine epoxy curing agent or an aromatic amine epoxy curing agent; the cation in the imidazole dispersing aid is one or two or three of 1,3-dimethylimidazolium cation, 1,2-dimethylimidazolium cation or 2,3-dimethylimidazolium cation.

7. A polymer capable of simultaneously releasing far infrared rays and negative ions according to any one of claims 1 to 5, characterized in that: The weight proportion of cerium group elements in the light rare earth powder is 0.5-5%; the coating interface agent is silver iodide and zinc dioxide, and the ratio of silver iodide to zinc dioxide is 30-70%:30-70%.

8. A polymer capable of simultaneously releasing far infrared rays and negative ions according to any one of claims 1 to 5, characterized in that: The particle sizes of the small molecule pure water color paste, epoxy resin emulsion, propylene glycol, epoxy curing agent, silver iodide powder, imidazole dispersing aid, rutile titanium dioxide powder, light rare earth powder, coating interface agent and special mineral powder are all nanometer grade.

9. The method for preparing a polymer capable of simultaneously releasing far infrared rays and negative ions according to any one of claims 1 to 8, characterized in that The following steps are involved: S1. Prepare raw materials in proportion; S2, adding small molecule pure water color paste, epoxy resin emulsion, propylene glycol and imidazole dispersing aid into a reaction vessel for mixing and pre-dispersing to obtain a mixture, and the mixing and pre-dispersing time is 30 to 180 minutes; S3, dividing the mixture obtained in S2 into two parts, and putting them into the first reaction kettle and the second reaction kettle respectively; S4, putting silver iodide and rutile titanium dioxide powder into a first reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 1, and the polymerization reaction time is 60 to 180 minutes; S5, putting light rare earth powder, coating interface agent, epoxy curing agent and mineral mixed powder into a second reaction kettle, and polymerizing the mixture obtained in S2 to obtain polymer 2, and the polymerization reaction time is 60 to 200 minutes; S6. Performing electrophoresis reaction on the obtained polymer 1 and polymer 2 at a voltage of 600 to 1000 V to generate a target polymer.

Citation Information

Patent Citations

  • Green environment-friendly multifunctional energy-night-storage nano-grade luminescent paint

    CN102898880A

  • Environment-friendly exterior wall coating and preparation method thereof

    CN105199604A

  • Antibacterial negative ion coating and preparation method thereof

    CN109535936A

  • Tourmaline far-infrared functional powder material and preparation method thereof

    CN111925198A

  • Nanometer antibacterial material and preparation method thereof, and antibacterial fiber material and application thereof

    CN111961251A